Efficacy study of olmesartan medoxomil on coronary atherosclerosis progression and epicardial adipose tissue volume reduction in patients with coronary atherosclerosis detected by coronary computed tomography angiography: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Zhou, Ying; Tian, Feng; Wang, Jing; Yang, Jun-Jie; Zhang, Tao; Jing, Jing; Chen, Yun-Dai
Abstract Background Epicardial adipose tissue (EAT) is a newly discovered independent risk factor for coronary atherosclerosis. There is a scarcity of information on the reduction of EAT volume to reduce atherosclerosis risk. Coronary computed tomography angiography (CCTA) has emerged as a noninvasive imaging method for the analysis of coronary atherosclerosis and EAT volume. The purpose of this trial is to determine whether olmesartan medoxomil is effective at both treatment of coronary atherosclerosis progression and EAT volume reduction in patients with coronary atherosclerosis detected by CCTA. Methods/design This study is a prospective, single-center, open-label, randomized controlled clinical trial aimed at exploring the efficacy of olmesartan medoxomil on coronary atherosclerosis and EAT. A total of 194 patients with coronary stenosis greater than 30 % and less than 70 % detected by CCTA will be randomly divided into olmesartan medoxomil or conventional antihypertensive medication groups (1:1 ratio). The primary outcome measures include coronary atherosclerosis progression and EAT volume reduction, as detected by CCTA at 12 months. The secondary outcome measures include the levels of blood lipids, glucose, high-sensitivity C-reactive protein, IL-6, monocyte chemotactic protein 1, TNF-α, matrix metalloproteinase 9, NO, endothelin 1, adiponectin, and leptin at baseline and after 6 and 12 months. Discussion Treatments aimed at reducing EAT volume can eventually achieve an antiatherosclerotic effect. This is the first trial designed to explore the effect of olmesartan medoxomil on both coronary atherosclerosis progression and EAT volume reduction in patients with coronary atherosclerosis detected by CCTA. Trial registration ClinicalTrials.gov:NCT02360956 .